2022
DOI: 10.1111/eea.13210
|View full text |Cite
|
Sign up to set email alerts
|

Following the track: accuracy and reproducibility of predation assessment on artificial caterpillars

Abstract: By initiating top-down trophic cascades, predators can indirectly control the amount of plant biomass consumed by insect herbivores in both natural and agricultural landscapes (Vidal & Murphy, 2018;Abdala-Roberts et al., 2019). As a key biotic interaction, predation has been an ecological process scrutinized by ecologists for decades (Holmes et al., 1979;Fowler & Knight, 1991;Mäntylä et al., 2011).Yet, predation is a fleeting phenomenon that is difficult to track in real time, especially because it has delayed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, another factor to be considered is the reliability of identification. The accuracy was 76% for identification in the categories of arthropods, birds and mammals by scientists with no previous experience (Valdés-Correcher et al 2022). Hence, it cannot be concluded that birds are the main herbivore predators in urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another factor to be considered is the reliability of identification. The accuracy was 76% for identification in the categories of arthropods, birds and mammals by scientists with no previous experience (Valdés-Correcher et al 2022). Hence, it cannot be concluded that birds are the main herbivore predators in urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, despite their indirect nature, these methods offer valuable insights into the effectiveness of predators in regulating herbivorous insect populations (Leles et al 2017). Using proxy baits, such as dummy caterpillars, is another approach to monitoring predation pressure (Howe et al 2009; Valdés-Correcher et al 2022). Predation pressure can be assessed based on attack rates on baits and compared between sites and treatments, provided that experimental setups are equivalent even though clay caterpillars lack many of the traits of natural caterpillars, which can skew the study toward generalist predators (Leles et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Clay models facilitate standardization across countries, and in theory enable researchers to distinguish among predator guilds based on attack marks left in clay (Howe et al, 2009). However, up to half the attack marks (and all missing prey) cannot reliably be assigned to a predator group (Bateman et al, 2017;Rodriguez-Campbell, 2023;Rößler et al, 2018), and ~20% of mark identifications are incorrect even when made by experienced scientists (Valdés-Correcher et al, 2022), casting doubt on the validity of predator group comparisons using attack marks.…”
Section: Introductionmentioning
confidence: 99%
“…Clay models facilitate standardization across countries, and in theory enable researchers to distinguish among predator guilds based on attack marks left in clay (Howe et al., 2009). However, up to half the attack marks (and all missing prey) cannot reliably be assigned to a predator group (Bateman et al., 2017; Rodriguez‐Campbell, 2023; Rößler et al., 2018), and ~20% of mark identifications are incorrect even when made by experienced scientists (Valdés‐Correcher et al., 2022), casting doubt on the validity of predator group comparisons using attack marks. Further, clay prey lack important sensory signals, such as movement, sound, thermal and scent cues, that are used to varying degrees among and within predator guilds including snakes, lizards, spiders, ants, and beetles (Bernays, 1997; Cooper, 2008; Ferrante et al., 2017; Herzog Jr & Burghardt, 1974; Reilly & McBrayer, 2007; Young, 2003).…”
Section: Introductionmentioning
confidence: 99%